Fault diagnosis of open-switch failure in a grid-connected three-level Si/Sic hybrid ANPC inverter - Kwon, Bong Hyun; Kim, Sang Hun; Kim, Seok Min; Lee, Kyo Beum (Electronics (Switzerland), 2020)
A diagnostic method for an open-circuit switch failure in a hybrid active neutral-point clamped (HANPC) inverter is proposed in this paper. The switching leg of the HANPC inverter consists of four silicon insulated gate bipolar transistors and two silicon carbide metal-oxide-semiconductor field-effect transistors to achieve higher efficiency and power density compared to conventional neutral-point clamped inverters. When an open-circuit failure occurs in a switching device, the output current is severely distorted, causing damage to the inverter and the connected loads. The proposed diagnostic method aims to detect the open-switch failure and protect the related devices without additional sensors or circuits. The faulty conditions of six different switches are investigated based on the current distortion in the stationary reference frame. By analyzing the individual characteristic of each switch failure, it is possible to detect the exact location of the failed switch in a short period. The effectiveness and feasibility of the proposed fault-diagnostic method are verified using simulation and experimental results.
Keywords: Active neutral-point clamped inverters; Fault diagnosis; Grid-connected systems; Open-circuit switch failure; Silicon carbide devices